Strengthening work engagement through digital engagement, gamification and psychosocial safety climate in digital transformation - Arief Nurkhori; Alfina Rahmatia; Sri Handari Wahyuningsih; Arni Surwanti (Faculty of Economics and Business, University of Muhammadiyah Malang, 2021)
The problem faced in technological developments and during the pandemic is transforming employee habits from offline to online work engagement. This research aims to look at empirical evidence regarding the relationship between digital engagement, gamification, and psychosocial safety climate (PSC) on work engagement. This study employs a quantitative approach with structural equation modelling, analyzing a series of exploratory and confirmatory factors to determine the relationship between variables. This study uses primary data through a questionnaire of as many as 164 respondents with a purposive sampling technique. This study proves that digital engagement and gamification variables on PSC and work engagement have a significant positive effect. Aspects of digital transformation through digital engagement and gamification influence PSC to increase work engagement. The relationship between gamification channelled through PSC can also mediate and prove a positive influence in strengthening work engagement.